Pengaruh Financial Literacy Terhadap Minat Masyarakat Menggunakan Produk Perbankan PT. BPR Araya Arta - Wahyuningsih, Sri; Sutriningsih, Sutriningsih; Triana, Endang Syta (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Understanding of financial literacy needs to be constantly improved in order to create opportunities for financial transactions in the banking world. Financial literacy education for the community plays an important role in banking because financial literacy will help the community in good financial management to avoid financial problems. Corona Virus 19 has an impact on the banking sector due to restrictions. The aim is to determine the effect of financial literacy on people's interest in using banking products. The population of this research is PT. Deposits at BPR Araya Arta for the last two years. The method used is descriptive quantitative with a sample of 100 respondents taken by purposive sampling. The analytical tool used is simple linear analysis with the help of the SPSS 25 program. The results of this study indicate that there is a significant influence between financial literacy and interest in PT. BPR Araya Arta is 31.7%, which means that financial literacy will have an impact on the use of products and services or transactions in financial institutions.